Self-healing epoxies using two-part epoxy-amine chemistry - Zhang He (2014)
Epoxy adhesives and epoxy based composites have been extensively applied in engineering fields due to their excellent properties. However, due to its relatively low fracture toughness, this thermosetting polymer is highly sensitive to the defects or cracks. How to toughen it and prolong its service life is one of the most practical and attractive topics. Among all the techniques developed, self-healing approach using micro-carriers has been demonstrating its promising potential since it can not only toughen the matrix by the included carriers, but also extend its lifespan by healing the induced micro-cracks timely using the reagents encapsulated in the micro-carriers. Although various techniques were explored to autonomously heal epoxy materials, amine-based curing chemistry as a major process of producing industrial epoxies indicates that a similar self-healing chemistry is needed in order to achieve a homogeneous and fully compatible healed structure. Therefore, it is demanded to explore two-part epoxy-amine self-healing systems with low cost, wide adaptability, and ease of processing, and most importantly, to develop robust micro-containers for amines with chemical and thermal stabilities in consideration of nature of amines and material processing requirements.